Conservative treatment for interstitial monochorionic twin pregnancy: Case report and review of the published work. Issue 3 (10th December 2013) - Berretta, Roberto; Merisio, Carla; Dall'Asta, Andrea; Verrotti, Carla; Rolla, Martino; Bruni, Stefano; Bacchi Modena, Alberto
Abstract Interstitial pregnancy is considered one of the most hazardous types of ectopic pregnancies, with a mortality rate of 2–2.5%. We describe a case of a viable monochorionic twin pregnancy in a 35‐year‐old woman successfully treated with systemic methotrexate associated with bilateral uterine arteries' embolization. β‐hCG was undetectable 67 days after the first administration of methotrexate and the ultrasonography performed on day 67 showed the remnant of the gestational sac in the right uterine horn, a thin endometrium and a normal myometrial vascularization. Conservative treatment allowed us to avoid surgical treatment and to preserve the patient's fertility.